Variation in bird assemblages and their invertebrate prey in eucalypt formations across a rainfall gradient in south-west Australia - Majer, Jonathan; Recher, H.; Norwood, C.; Heterick, Brian (Surrey Beatty and Sons, 2017)
Our previous work has shown how invertebrate food resources influence usage of tree species by birds. Using data from Western Australian forests and woodlands, we extend the findings to indicate how the avifauna is influenced by these resources at the landscape level. The northern dry sclerophyll forest of south-west Australia comprises jarrah (Eucalyptus marginata) to the west, with an abrupt replacement by wandoo (E. wandoo) plus powderbark wandoo (E. accedens) woodland to the east; codominant marri (Corymbia calophylla) trees occur throughout. Knockdown samples have previously indicated that the canopy invertebrate fauna is richer and more abundant in wandoo woodland than in jarrah/marri forest. To provide an indication of their general abundance and diversity in these formations, invertebrates using the trunks of the ubiquitous marri were measured along a transect from jarrah/marri forest to wandoo woodland. Mirroring the canopy, the trunk fauna had high species turnover over short distances. As with the canopy fauna, invertebrate diversity and abundance was higher on marri situated in the wandoo zone than in the jarrah/marri areas, indicating a generally larger invertebrate fauna in the drier regions of the transect. Abundance and diversity of birds, many of which are wholly or partly insectivorous, were measured at the same sites. Birds were more abundant and there were more species in areas with the wandoo species than in those dominated by jarrah/marri. Assemblage composition also differed in the two forest types. It is evident that changes in bird abundance, richness, and assemblage composition are likely determined on a landscape scale by the type, abundance, and diversity of food resources available to them. These patterns of change within forest invertebrate faunas and their primary vertebrate predators need to be considered when making decisions on conserving or managing forest communities in Australia.